Peningkatan Kapasitas UMKM Batik Rosela melalui Diversifikasi Produk dan Pemasaran Digital - Adelita Zahrah; Griffith Athalla Eriawan; Serlinda Mareta Putri; Dewi Deniaty Sholihah (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
challenges in product diversification and the use of digital marketing channels. This community service program aims to enhance the capacity of the MSME through the development of handkerchief souvenirs and the utilization of digital media for promotional activities. The program was implemented by Group 107 of the KKNT SDGs Bela Negara, Universitas Pembangunan Nasional “Veteran” Jawa Timur, using a participatory approach and involving 35 participants. The stages of implementation include preliminary observation, training on producing handkerchiefs with Javanese and Korean motifs, product photography training, and assistance in managing social media accounts. The results indicate an improvement in the partners’ skills in producing simple yet appealing souvenirs, along with initial abilities in creating content and using digital platforms to expand market reach. Overall, this program contributes to strengthening MSME competitiveness, enhancing local product identity, and serving as an initial step toward the sustainable digital transformation of Batik Rosela MSME.